2012
DOI: 10.1002/j.1681-4835.2012.tb00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Animated Videos as a Learning Tool in Developing Nations: A Pilot Study of Three Animations in Maradi and Surrounding Areas in Niger

Abstract: Access to information and knowledge has always been a challenge for illiterate or low literate learners in developing nations. As a consequence, pedagogical advances, for low literate learners, have lagged behind, as compared to educational strategies for literate or highly literate learners. The technological revolution based on access to Internet and cell-phones has brought new opportunities to one billion low literate learners in the planet. There is evidence that cell-phones are becoming easily available f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
(8 reference statements)
2
15
0
Order By: Relevance
“…Educational programs should help to locate and address the different gaps and motivate processors to ensure better quality to meet international demands while at the same time position themselves to control the increase returns for their labor and knowledge. Bello-Bravo and Baoua [62] observed that when showing SAWBO videos in Niger, those that observed these videos often talked at length about other education needs in their community. Thus, such educational tools also represent a potential two-way dialogue where ideas from the field (such as indigenous knowledge) can be incorporated into additional educational animations and then used in future educational programs [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational programs should help to locate and address the different gaps and motivate processors to ensure better quality to meet international demands while at the same time position themselves to control the increase returns for their labor and knowledge. Bello-Bravo and Baoua [62] observed that when showing SAWBO videos in Niger, those that observed these videos often talked at length about other education needs in their community. Thus, such educational tools also represent a potential two-way dialogue where ideas from the field (such as indigenous knowledge) can be incorporated into additional educational animations and then used in future educational programs [61].…”
Section: Discussionmentioning
confidence: 99%
“…All videos can also be downloaded through both of SAWBO's websites, a full version and a mobile version (for people with low bandwidth) or through the online system known as the "Sustainable Development Knowledge Interface" (SusDeViKI) [59][60][61][62]. Thus, for development groups, that wish to use these videos in their educational programs, they can easily access the necessary content from the Internet for deployment into the field on cell phones.…”
Section: Potential Of Ict Use To Enable Empowerment Of Women In a Shementioning
confidence: 99%
“…While research shows that people from diverse cultural groups are generally open to learning from the same or similar sets of culturally non-specific animated images, dialectical inaccuracy of voiceovers is reported as off-putting and can diminish the effectiveness of ICT knowledge transfer (Bello-Bravo & Baoua, 2012;BelloBravo, Dannon, Agunbiade, Tamò, & Pittendrigh, 2013;Bello-Bravo, Dannon, et al, 2017;Bello-Bravo, Olana, Enyadne, & Pittendrigh, 2013;Bello-Bravo, Seufferheld, et al, 2013). Addressing people in their own language is not only communicatively pragmatic (Nonaka & Takeuchi, 1995) but can also mitigate any on-going, oppressive power dynamics around the use of ex-colonial or national languages in Africa (Kiramba, 2016), thus better fostering trust in any solutions communicated (Levin & Cross, 2004;Szulanski, Cappetta, & Jensen, 2004) and making them potentially more authoritative, credible, and liable for uptake (Bello-Bravo, Lutomia, Madela, et al, 2017).…”
Section: Study Purpose and Theoretical Frameworkmentioning
confidence: 99%
“…As shown in figure 1, around 25 (44%) of the reviewed papers fall in this category. Specifically, the following list of papers': (Amariles et al, 2007;Baro & Endouware, 2013;Bello-bravo & Baoua, 2012;Cáceres & Fernández-Ardèvol, 2012;Cloete & Doens, 2008;Dearden et al, 2011;Dearden et al, 2010;Dissanayeke & Wanigasundera, 2014;Dittoh et al, 2013;Lwoga, 2010;Futterman & Shuman, 2010;Gollakota et al, 2012;Kameswari et al, 2011;Kuriyan et al, 2006;Madon et al, 2009;Martin & Abbott, 2011;Mpazanje et al, 2013;Muthiah et al, 2013;Srinivasan, 2007;Patel et al, 2012;Siyao, 2012;Tomitsch et al, 2010;Mtega & Msungu, 2013;Yusop et al, 2013), main study areas focus on understanding context and documenting best practices. For instance, over five months field pilot of a voice telephony-based information service, (Futterman & Shuman, 2010) and (Yusop et al, 2013) assess the information needs and interests of rural populations in Uganda and Malaysia respectively.…”
Section: S O U R C Ementioning
confidence: 99%